2017
DOI: 10.1016/j.jtho.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stereotactic Ablative Radiotherapy (SABR) in Non–Small Cell Lung Cancer Measuring More Than 5 cm

Abstract: Lung SABR in tumors larger than 5 cm resulted in high local control rates and acceptable survival outcomes in a patient population with appreciable comorbidity. Patients with interstitial lung disease should be considered a very high-risk population for SABR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
(49 reference statements)
0
19
2
1
Order By: Relevance
“…First, critical nearby normal tissue dose constraints such as esophagus, bronchial tree, brachial plexus, heart, major vessels etc. may limit the ablative dose that could be safely delivered (8); second, the efficacy of SBRT is reduced and toxicity is increased with increasing size of the lesion, particularly when the lesion is >5 cm (9). Most of SBRT's outstanding clinical outcomes reported in the literature are based on lesions less than 5 cm, typically <3 cm, and are not close/next to critical normal structures.…”
Section: Rt-treatment For Local Controlmentioning
confidence: 99%
“…First, critical nearby normal tissue dose constraints such as esophagus, bronchial tree, brachial plexus, heart, major vessels etc. may limit the ablative dose that could be safely delivered (8); second, the efficacy of SBRT is reduced and toxicity is increased with increasing size of the lesion, particularly when the lesion is >5 cm (9). Most of SBRT's outstanding clinical outcomes reported in the literature are based on lesions less than 5 cm, typically <3 cm, and are not close/next to critical normal structures.…”
Section: Rt-treatment For Local Controlmentioning
confidence: 99%
“…Die Erfahrungen der SBRT beruhen überwiegend auf Tumoren mit einem Durchmesser < 5 cm: Bei größeren Tumoren kommt es zu einer vermehrten Normalgewebsbelastung mit assoziiertem erhöhtem Nebenwirkungsrisiko. In einigen retrospektiven Arbei-ten zur SBRT bei primären Lungentumoren mit einem Durchmesser > 5 cm wurden vielversprechende onkologische Ergebnisse beschrieben und auch die Toxizität erscheint akzeptabel, in einzelnen Arbeiten aber erhöht im Vergleich zur Bestrahlung kleinerer Tumoren [51][52][53].…”
Section: Risikosituationen Für Sbrtunclassified
“…A report on outcomes of SABR in tumors exceeding 5 cm suggested that high local control rates and acceptable survival outcomes were achieved in patients without coexisting interstitial lung disease. 24 In patients with lung cancer and coexisting interstitial lung disease who underwent SABR, a systematic review reported a weighted proportion of treatment-related deaths of 15.6%. 25 In the 2017 American Society for Radiation Oncology guidelines, SABR was considered an appropriate option for tumors exceeding 5 cm if physicians endeavored to adhere to the constraints that had been utilized in prospective studies.…”
Section: Introductionmentioning
confidence: 99%